1996
DOI: 10.2466/pr0.1996.79.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cervical Cancer Screening Using the Theory of Reasoned Action

Abstract: Rates of Pap smears among 72 adult women were shown to be suboptimal and predicted indirectly by attitudes and subjective norms. Women perceived these examinations to be unpleasant and embarrassing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…In accordance with other studies, [12][13][14]30 physicians' identification of the presenting problem being a priority, lack of a reminder system, women's fear of the Pap test, and discomfort during mammography as barriers to cancer screening bring to the forefront the need for systemic restructuring and public health promotion efforts. For example, the time constraints of physicians and patients can be reduced by emphasizing the benefits of periodic health visits.…”
Section: Gender Analysis Of Cancer Screening 205supporting
confidence: 84%
“…In accordance with other studies, [12][13][14]30 physicians' identification of the presenting problem being a priority, lack of a reminder system, women's fear of the Pap test, and discomfort during mammography as barriers to cancer screening bring to the forefront the need for systemic restructuring and public health promotion efforts. For example, the time constraints of physicians and patients can be reduced by emphasizing the benefits of periodic health visits.…”
Section: Gender Analysis Of Cancer Screening 205supporting
confidence: 84%
“…They were selected because components of these models have been useful in predicting Papanicolaou smear screening beliefs and behaviors. [22][23][24][25][26][27][28][29][30] The health belief model hypothesizes that preventive health behavior depends on the desire to avoid illness and the belief that a specific health action will prevent illness. Its dimensions include perceived susceptibility to illness, perceived severity of an illness or of leaving it untreated, perceived benefits of recommended actions to prevent or treat a disease, and perceived barriers to following recommendations.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Other investigators have demonstrated that components of these models are useful in predicting adult women's cervical cancer screening beliefs and behavior. [22][23][24][25][26][27][28][29][30] These studies provide valuable information, but have addressed only the beliefs and behaviors of young adult and adult women. In our analysis, although each model provided insight into the predictors of Papanicolaou smear follow-up, no single theory emerged as explanatory.…”
Section: Commentmentioning
confidence: 99%
“…(3) A bivariate statistical relationship between cognitions and intention (or behaviour) had to be retrievable. Where reports did not include relevant statistics (e.g., Barling & Moore, 1996), the authors of the study were contacted and requests were made for bivariate associations.…”
Section: Literature Review and Inclusion/exclusion Criteriamentioning
confidence: 99%